Study on the best growing variety of onion on the hilly land of Jeli, Kelantan, Malaysia - Nor Razanah Che Ibrahim; S.M. Rezaul Karim (2012)
Onion (Allium cepa L.) is one of the most important spice and vegetable in the daily diet of entire world not only among Malaysian citizens. Unfortunately little discover on this crop in Malaysia, thus it made almost 100% of this vegetable comes from foreign country. Therefore since hilly land of Jeli is cool climate, planting of 6 varieties of onion cultivar from Bangladeshi which is Ono:275, Ono:276, Ono:277, Ono:285, Ono:286 and Ono:287 were carried out at Batu 17, Jeli. The aim of this study is to determine the best variety that can be grown and suited for cultivation in high land regions on Malaysia. Germination test were done on all varieties shown that average rate of seed germination exceed 80%. Methods of transplanting were used by growing the seedling in the seed trays. Results indicated that parameters of plant height, number of leaves per plant, perimeter of the bulb and weight of the bulb were leads by Ono: 276.